Optimalisasi Penggunaan Aplikasi Open SID pada Sistem Administrasi Pemerintah Desa Gabusbanaran - Muhammad Farid Nasrulloh; Priyo Wahono; Fitriah Nur Amanah; Chuliyatul Mufarrohah; Wisnu Siwi Satiti (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
Knowledge of information technology has become a requirement that must be met by someone. This is because most of a person's daily activities involve information technology assistance, both teaching and learning activities, working in agencies and entrepreneurship. In addition, knowledge of information technology is a person's main capital to be able to compete in the era of globalization and the progress of the times to come. This service is carried out in Gabusbanaran Village, Tembelang District, Jombang. The purpose of this service is to focus on optimizing the Village Information System (SID) application, adapting the Village Information System (SID) application to the needs of village administration, and providing an understanding of the use of the Village Information System (SID) application. The method of implementing the activities aims to find solutions to the problems experienced by the village government in inputting data. This is done with work procedures that support the realization of making application systems. The service method uses the ABCD (Asset Based Community Development) approach, which is a method by utilizing assets owned by the local community which is seen as being able to support community empowerment activities. The results of community service in optimizing the Village Information System (SID) application are providing additional insight and knowledge and skills to the ranks of Gabusbanaran village officials regarding village information systems, assisting in disseminating information quickly and thoroughly through the website and making it easier for the community to get information from the village.